Traumatic brachial arteriovenous fistula - Adil Ayub; Sareema Adnan; Grant Fankhauser; Kanika Bowen-Jallow; Sifrance Tran (Elsevier, 2019)
Acquired arteriovenous fistula (AVF) are rare in the pediatric population. We report a 15-year-old boy who sustained a ballistic ball (BB) gun pellet injury to the left forearm leading to formation of a traumatic branchio-brachial AVF. He underwent successful open repair of his fistula using a vein patch graft. We share our management of this rare case and review management of pediatric arteriovenous fistulas. Keywords: Arteriovenous fistula, Traumatic, Pediatric, Acquired